Micropartículas de poli (ácido lático-co-ácido glicólico) obtidas por spray drying para a liberação prolongada de metotrexato - Oliveira, Alice Rodrigues de (2011)
Methotrexate (MTX) is a drug used in the chemotherapy of some kind of cancers, autoimmune diseases and non inflammatory resistant to corticosteroids uveits. However, the rapid plasmatic elimination limits its therapeutic success, which leads to administration of high doses to maintain the therapeutic levels in the target tissues, occurring potential side effects. The aim of this study was to obtain spray dried biodegradable poly-lactic acid co-glycolic acid (PLGA) microparticles containing MTX. Thus, suitable amounts of MTX and PLGA were dissolved in appropriate solvent system to obtain solutions at different ratios drug/polymer (10, 20, 30 and 50% m/m). The physicochemical characterizing included the quantitative analysis of the drug using a validate UV-VIS spectrophotometry method, scanning electron microscopy (SEM), infrared spectrophotometry (IR), thermal analyses and X-ray diffraction analysis. The in vitro release studies were carried out in a thermostatized phosphate buffer pH 7.4 (0.05 M KH2PO4) medium at 37°C ± 0.2 °C. The in vitro release date was subjected to different kinetics release models. The MTX-loaded PLGA microparticles showed a spherical shape with smooth surface and high level of entrapped drug. The encapsulation efficiency was greater then 80%. IR spectroscopy showed that there was no chemical bond between the compounds, suggesting just the possible occurrence of hydrogen bound interactions. The thermal analyses and X-ray diffraction analysis shown that MTX is homogeneously dispersed inside polymeric matrix, with a prevalent amorphous state or in a stable molecular dispersion. The in vitro release studies confirmed the sustained release for distinct MTX-loaded PLGA microparticles. The involved drug release mechanism was non Fickian diffusion, which was confirmed by Kornmeyer-Peppas kinetic model. The experimental results demonstrated that the MTX-loaded PLGA microparticles were successfully obtained by spray drying and its potential as prolonged drug release system.